Changes in Brassica oleracea Leaves Infected With Xanthomonas campestris pv. campestris by Proteomics Analysis - Tortosa, María; Velasco, Pablo; Rodríguez, Víctor Manuel; Cartea, María Elena (Frontiers in Plant Science, 2022)
Understanding plant’s response mechanisms against pathogenesis is fundamental for the development of resistant crop varieties and more productive agriculture. In this regard, ‘omic’ approaches are heralded as valuable technologies. In this work, combining iTRAQ technology with mass spectrometry, the proteomes from leaves of Brassica oleracea plants infected with Xcc and control plants at two different post-infection times were compared. Stronger proteomic changes were obtained at 12 days post-infection in comparison with 3 days. The responses observed involved different cell processes, from primary metabolism, such as photosynthesis or photorespiration, to other complex processes such as redox homeostasis, hormone signaling or defense mechanisms. Most of the proteins decreased in the earlier response were involved in energetic metabolism, whereas later response was characterized by a recovery of primary metabolism. Furthermore, our results indicated that proteolysis machinery and ROS homeostasis could be key processes during this plant-pathogen interaction. Current data provide new insights into molecular mechanisms that may be involved in defense responses of B. oleracea to Xcc.